Profil Kemampuan Literasi Statistis Mahasiswa Teknik Sipil Universitas Katolik Indonesia Santu Paulus Ruteng Ditinjau Dari Gender - Murni, Viviana; Jehadus, Emilianus; Sugiarti, Lana (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
Statistical literacy is an important competency that Civil Engineering students must possess in processing and interpreting statistical data to support decision-making in the engineering field. However, previous research has shown differences in statistical literacy based on gender. Therefore, this study aims to describe the profile of statistical literacy skills of Civil Engineering students in terms of gender differences. This study uses a descriptive qualitative approach with research subjects consisting of 15 male and 15 female Civil Engineering students. Data were collected using a statistical literacy test that includes 4 indicators, namely (1) aspects of reasoning towards statistical data and results, (2) reasoning towards basic statistical concepts and statistical terms, (3) reasoning towards descriptive data collection and processing, and (4) data interpretation. Data were analyzed through stages such as data reduction, data presentation, and conclusions. The results of the analysis show that the achievements of female and male students for each indicator vary. In 3 indicators, female students are at the relational level. They are at the unistructural level in the fourth indicator. Meanwhile, male students are at the unistructural level in the first indicator, multistructural level in the second and third indicators, and prestructural level in the fourth indicator. The implication is that efforts are needed to improve statistical literacy skills, especially for male Civil Engineering students, so they can optimally prepare themselves to face the challenges of statistics in the engineering field.